2010
DOI: 10.2136/vzj2009.0177
|View full text |Cite
|
Sign up to set email alerts
|

Water Flow Monitored by Tracer Transport in Natural Porous Media Using Magnetic Resonance Imaging

Abstract: Magne c resonance imaging (MRI) was applied to the study of fl ow processes in model and natural soil cores. Flow veloci es in soils are mostly too slow to be monitored directly by MRI fl ow velocity imaging. Therefore, we used for the fi rst me diethylenetriaminepentaacetate in the form Gd-DTPA 2− as a tracer in spin echo mul slice imaging protocols with strong weigh ng of longitudinal relaxa on me T 1 for probing slow fl ow veloci es in soils. Apart from its chemical stability, the main advantage of Gd-DTPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…Similar observations of Gd-DTPA migration with the tracer were reported by Haber-Pohlmeier et al (2010), who showed that Gd-DTPA behaves conservatively in sand and in a natural soil core. They reported no retention and explained that the Gd-DTPA is not adsorbed due to its large size.…”
Section: Resultssupporting
confidence: 88%
“…Similar observations of Gd-DTPA migration with the tracer were reported by Haber-Pohlmeier et al (2010), who showed that Gd-DTPA behaves conservatively in sand and in a natural soil core. They reported no retention and explained that the Gd-DTPA is not adsorbed due to its large size.…”
Section: Resultssupporting
confidence: 88%
“…For the simulation of water flow, a three‐dimensional, cell‐centered, finite‐volume code was used (Ippisch et al, 2006; Rossi et al, 2008; Carminati and Flühler 2009; Haber‐Pohlmeier et al, 2010; Bechtold et al, 2011b) that solves the Richards equation: leftθ(h)t=θuleft=[K(θ)h]+K(θ)z where h is pressure head (cm), u is the pore water velocity vector (cm d −1 ), K is hydraulic conductivity (cm d −1 ), and z is the vertical coordinate directed positively upward (cm). The variables θ( h ) and K (θ) were described by the van Genuchten–Mualem parametric expressions (van Genuchten 1980) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Early MR studies already showed the effects of image distortion and signal loss in various types of soil (Bottomley et al, 1986). To minimize image distortions and in an effort to optimize MR relaxation parameters, sand was used as a medium for the latest MR studies (Haber‐Pohlmeier et al, 2010; Stingaciu et al, 2013). The researchers used a multislice, multi‐echo spin echo MR experiment.…”
Section: On the Magnetic Resonance Signal Of Plant Roots And Soilmentioning
confidence: 99%
“…The first studies focused on the ability to image roots, depending on soil conditions and an added MR contrast agent (Omasa et al, 1985; Bottomley et al, 1986; MacFall et al, 1991). Recent publications have reported the use of fast imaging techniques to reduce imaging time for the three‐dimensional acquisition of root images (Haber‐Pohlmeier et al, 2010) and the use of single‐point imaging (SPI) in systems with low water content (Gruwel et al, 2004). When the water content becomes low and the water MR signal starts to broaden, conventional MRI fails to produce an image while SPI can still provide useful images.…”
mentioning
confidence: 99%